The Development of Animation Video-Based Learning Media for Introducing Discipline to Children Aged 4-5 Years - Muntiani, Titik; Karim, M. Busyro; Nazarullail, Fikri (Jurnal Pendidikan Anak, 2021)
This research aims to develop Mehe's video-based learning animation "Aku Anak Disiplin" to introduce discipline in children aged 4-5 years. Subject in this research and development that is children 4-5 years in Early childhood education institution Anna Husada Bangkalan. Research and development this using the model Borg and Gall. Data techniques using questionnaire (media experts questionnaire, material experts questionnaire, and child question response). Media's feasibility based on the results of the media experts is obtaining the percentage 83.5%, based on the results of the experts of the material obtained a percentage of 85%. Media's feasibility based on product test results obtained a percentage of 96%. So, it can be concluded that media learning video animation "Aku Anak Disiplin" worth it is used to introduced discipline in children aged 4-5 years.